Linguistic and cultural aspects in animistic idioms defying personal character traits in English and Ukrainian (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2018)
The problem of studying national and ethnic-cultural components is an actual trend in contemporary linguistic studies, since linguistic elements manifest distinct national marking. The idea of language and culture interconnection belongs primarily to William von Humboldt. The language units can be treated as the specific treasury that preserves national identity of a certain language community. O. Potebnya expressed his own original vision of idioms, which he considered as a small version of the “whole world”. Having symbolic correlation with cultural signs, experience and behaviour stereotypes idioms represent universal ideas common to different language systems. Nevertheless there are also peculiar images belonging only to certain language groups and its interpretation demands deeper language and cultural code analysis. This research mainly focuses on studying idioms expressing the traits of character and behavioral habits through the animistic phraseological structures while bilingual teaching of English and Ukrainian in particular. The diversity of idioms with animistic components in their structure is rather various and can be hardly illustrated in one research. That is why the main attention of this study is paid to idioms with animistic components representing the following images: domestic animals and insects. The first group includes set expressions, which are distinguished according to the presence in their structure such words as a dog, a sheep, a hen. Illustration analysis shows that these animistic components are represented in both languages. Furthermore some idiomatic constructions demonstrate similar meaning and structure. The second group comprises comparatively smaller number of samples. It contains idioms defying rather emotional state of a person and his / her behavior rather personal character trait itself. The analysis of English and Ukrainian illustrations demonstrates the low correspondence of samples in both languages. Despite the fact that the world vision in both nations contains similar ideas about emotional state of a person and his / her behavior, its linguistic representation is totally different. The results of practical analysis vividly confirm the idea of national and cultural marking revealed in set expressions for both languages. It also shows the necessity of profound investigating national and cultural symbols while studying language phraseological and paremian heritage. These observations might help in highlighting more complicated world perception characteristics in English and Ukrainian.
Keywords: set expression; national and cultural peculiarities; language community; traits of character; animistic component